Our revolution : a future to believe in - Sanders, Bernard (2016)
The break-out Democratic candidate for president, who gave Hillary Clinton a run for her money, offers an inside account of his extraordinary campaign and a blueprint for future political action.
[Table of contents]. Running for President -- How do we turn out the way we do? -- My political life in Vermont -- Thinking about running -- How do you run a presidential campaign? -- The campaign begins -- On the campaign trail -- An agenda for a new America: how we transform our country -- Defeating oligarchy -- The decline of the American middle class -- Ending a rigged economy -- Health care for all -- Making higher education affordable -- Combatting climate change -- Real criminal justice reform -- Immigration reform now -- Protecting our most vulnerable -- Corporate media and the threat to our democacy -- Conclusion.
Keywords: Sanders, Bernard; Sanders, Bernard -- Political and social views; United States. -- Congress. -- House -- Biography; Presidents -- United States -- Election -- 2016.; Presidential candidates -- United States -- Biography; Legislators -- United States -- Biography; United States -- Politics and government -- 1989-